ЧИСЕЛЬНЕ МОДЕЛЮВАННЯ ТЕПЛОВОГО СТАНУ ІНДУКЦІЙНОЇ КАНАЛЬНОЇ ПЕЧІ - Бондар, О.І.; Глухенький, О.І.; Гориславець, Ю.М.; Западинчук, О.П. (Інститут електродинаміки НАН України, Київ, 2021)
A mathematical model that describes heat and mass transfer processes in an induction channel furnace is presented. Using the example of a two-phase channel furnace with standard form of channels, the influence of the phase angle between the voltages supplying the furnace inductors on the thermal state of the liquid metal is considered. Values of this angle, which provide minimal melt overheating in channels in comparison with furnace bath have been determined. Ways of intensification of heat and mass transfer processes in two-phase channel furnace have been suggested. References 9, figures 4.